Mechanically robust and high-performance ternary solar cells combining the merits of all-polymer and fullerene blends. Issue 10 (21st February 2018) - Lee, Wonho; Kim, Jae-Han; Kim, Taesu; Kim, Seonha; Lee, Changyeon; Kim, Jin-Seong; Ahn, Hyungju; Kim, Taek-Soo; Kim, Bumjoon J.
Abstract : In this work, we present a facile strategy that combines the merits of both fullerene-PSCs and all-PSCs to significantly increase the PCE of the all-PSCs without compromising mechanical performance. Abstract : In this study, we demonstrate that the introduction of small amounts of phenyl-C71 -butyric acid methyl ester (PC71 BM) into all-polymer solar cells (all-PSCs) increases the photovoltaic performance without compromising mechanical properties. Ternary blend polymer solar cells (ternary-PSCs) consisting of a polymer donor (PTB7-Th) and an acceptor mixture with different weight ratios of a polymeric acceptor (P(NDI2HD-T2)) and PC71 BM demonstrate the effects of PC71 BM loading on the power conversion efficiency (PCE) and mechanical properties. A significant enhancement in the PCEs of ternary-PSCs, from 6.32% to 7.33%, is observed when PC71 BM is added into the active layer as up to 30 wt% of the acceptor mixture. Importantly, the excellent mechanical properties ( i.e., crack onset strain = 11.6%, toughness = 2237 J m −3 ) of the blend films are well preserved at PC71 BM loadings at or below 30 wt%. In contrast, both the PCE and the mechanical performance of the ternary-PSCs significantly decrease at higher PC71 BM loadings (>50 wt%). Detailed morphological analysis via grazing incidence X-ray scattering measurements reveals that PC71 BM molecules are well-dispersed in the amorphous portion of the active layer at PC71 BM loadings up to 30 wt%. Therefore, both the mechanical and photovoltaic performances of the ternary-PSCs correlate closely with their morphological behavior, particularly in terms of the mixing behavior of PC71 BM with polymers. The well-dispersed PC71 BM molecules in the amorphous polymer domains facilitate efficient exciton dissociation, whereas the formation of PC71 BM aggregates above a critical concentration causes severe mechanical degradation of the ternary-PSCs due to the presence of weak interfaces between the brittle PC71 BM and polymer domains. Therefore, the ternary blends with optimal content of polymer/fullerene acceptors represent important candidates for flexible and wearable solar cells that require both high mechanical and photovoltaic performances.